Surgery in pregnancy: Identifying factors contributing to variation and delay in diagnosis and management of appendicitis in pregnancy. (28th December 2020) - Copson, Sean; Nathan, Elizabeth
Abstract : Background: Suspected appendicitis is the most common indication for surgery for non‐obstetric conditions during pregnancy. Delay in management increases the risk of appendiceal perforation and pregnancy loss. Stand‐alone specialty obstetric hospitals often don't have surgical teams on site. It has been suspected that this may be a factor that leads to delayed diagnosis and management of non‐obstetric surgical conditions in pregnancy. Aims: To assess the differences in time to diagnosis, imaging, surgical management and outcomes between a stand‐alone tertiary obstetric hospital and a tertiary general hospital for pregnant patients presenting with suspected appendicitis who underwent an appendicectomy. Materials and Methods: A retrospective study of all women who underwent appendicectomy in pregnancy for suspected appendicitis over a four‐year period. Results: Women who attended the specialist hospital were later in gestation (medians 29 weeks vs 18 weeks, P  = 0.004) and less likely to have imaging (84% vs 56%, P  = 0.047) with no difference in the rates of confirmation of diagnosis of appendicitis using imaging. Women who presented to the specialist hospital were more likely to be managed with a laparotomy, admitted to high dependency unit, have a longer hospital stay and tended to be later in gestation. There was no difference in rates of positive appendicectomies, appendiceal perforation or management in under the recommended 24 h. Conclusions: The specialty obstetric hospital has a much higher rate of laparotomy and longer length of stay. The majority of patients presenting to both hospitals did not undergo surgery within 24 h and delay in imaging was a major contributor.